2019
DOI: 10.1167/iovs.19-27258
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Inflammatory Proteins in Cord Blood as Predictive Biomarkers of Retinopathy of Prematurity in Preterm Infants

Abstract: PURPOSE. To determine whether elevated levels of immune/inflammatory proteins in cord blood, alone or in combination with conventional clinical parameters, can predict the occurrence and progression of retinopathy of prematurity (ROP) in preterm infants. METHODS. This was a retrospective cohort study of 110 premature singleton infants who were born at 32.0 weeks. Cord plasma at birth was assayed for interleukin-6, C3a, C5a, matrix metalloproteinase-2 (MMP-2), MMP-9, tissue inhibitor of metalloproteinase-1, mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Previous studies, including ours, also noted (i) elevated cord plasma levels of IL-6, C3a, and C5a, and (ii) events in the intrauterine environment that trigger spontaneous preterm delivery are significantly associated with an increased risk of ROP progression. 13 , 32 , 33 Taken together, these findings suggest that pathophysiologic events that predispose preterm neonates to ROP begin before delivery and that therapeutic strategies to decrease the risk of ROP may need to be implemented during pregnancy (e.g., specific treatment with antibiotics, anti-inflammatory drugs, and/or antiangiogenic drugs). Additionally, our findings strongly support the theory of Lee and Dammann 34 regarding the important etiological role of antenatal factors, especially prenatal and perinatal infection/inflammation, in ROP.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies, including ours, also noted (i) elevated cord plasma levels of IL-6, C3a, and C5a, and (ii) events in the intrauterine environment that trigger spontaneous preterm delivery are significantly associated with an increased risk of ROP progression. 13 , 32 , 33 Taken together, these findings suggest that pathophysiologic events that predispose preterm neonates to ROP begin before delivery and that therapeutic strategies to decrease the risk of ROP may need to be implemented during pregnancy (e.g., specific treatment with antibiotics, anti-inflammatory drugs, and/or antiangiogenic drugs). Additionally, our findings strongly support the theory of Lee and Dammann 34 regarding the important etiological role of antenatal factors, especially prenatal and perinatal infection/inflammation, in ROP.…”
Section: Discussionmentioning
confidence: 95%
“…Similar to the current findings in AF, our recent study using cord blood samples at birth, showed that elevated levels of cord plasma IL-6 were significantly associated with severe ROP. 13 Furthermore, previous studies using postnatal blood have demonstrated that inflammatory proteins are significantly elevated in the peripheral blood obtained in the postnatal period of preterm infants with ROP. 6 9 , 11 , 12 Therefore, these findings show that in utero to postnatal systemic inflammation is linked to ROP occurrence and progression, and highlight the importance of inflammation in the pathogenesis of ROP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal inflammation [105][106][107] and nutritional deficiencies [108][109][110] are postulated to render the developing retina more susceptible to ROP pathogenesis. Nutritional deficiencies in polyunsaturated fatty acids (PUFAs), inositol, vitamins A, E, and D supplied in human breast milk (BM) are known to increase inflammation and oxidative stress and therefore these processes are likely inter-related.…”
Section: Human Breast Milkmentioning
confidence: 99%
“…However, other vascular and inflammatory proteins as well as growth factors, angiogenetic proteins, and neurotrophins have also been suggested to be associated with ROP. [6][7][8][9][10][11] This multitude of ROP-associated factors demonstrates that numerous signaling pathways may be involved in the development of ROP and that maybe not a single biomarker but a combination of biomarkers should be investigated.…”
Section: Introductionmentioning
confidence: 99%